An investigation into the teaching-learning environment of the Faculty of Management and Human resource Development: towards the establishment of an optimal environment for the pursuit of excellence in teaching and learning - Selamat, Ruzita; Ungku Ahmad, Ungku Norulkamar; Abd. Razak, Noor Zainab; Ali, Lokman; Abdul Aziz, Azian; Sheik Ahmad, Fauziah; Ahmad Khalid, Aminah (Faculty of Management and Human Resource Development, 2004)

(untitled)
A conducive teaching and learning environment is one of the elements which influence the effectiveness of the knowledge transmitted and received. Providing a good teaching and learning environment will help enhance the development of the university into becoming a world class university. The aim of this research is to identify lecturers’ and students’ perception towards the teaching and learning environment of the Fakulti Pengurusan dan Pembangunan Sumber Manusia (FPPSM), UTM, and to gain feedback from the lecturers and students on how to increase the effectiveness of the teaching and learning environment of FPPSM. Two sets of questionnaires have been distributed. One set was distributed to the lecturers while another set was distributed to the students. The teaching and learning environment studied comprise of the physical and the administrative aspects of the faculty that have an impact on teaching and learning in FPPSM i.e infrastructure, equipments and administrative and clerical support. Results show that lecturers feel the class rooms and resource room in FPPSM are not conducive for teaching and learning. Nevertheless, they are satisfied with the cyberpreneur room and the facilities provided. On the other hand, students are not satisfied with all the aspects of teaching and learning environment studied. Based on the result of this study, several changes are suggested to be done in FPPSM in order to increase the effectiveness of the present teaching and learning environment.